(untitled) (Indian Journal of Public Health Research & Development, 2025)
Background & Objectives: Social media has grown to be the most influential and important virtual space that has revolutionized the digital world since its inception across diverse settings, but has also increased the rate of cybercrimes committed against women. This study was aimed to estimate the prevalence of cyberbullying, types and its association with sociodemographic variables among women residing in a rural community at southern Kerala Methods: A cross-sectional study was conducted among 289 women in a rural community in Thiruvananthapuram district, Kerala using a predesigned, pretested interviewer administered questionnaire. Results: Cyberbullying was found to be prevalent (10.4%) and the most common form of cyber bullying was impersonation (40%) and (33.33%) of them reacted by deleting their accounts. Majority (52.2%) of the participants belong to the age group of (31 – 45) years, were graduates (62.3%), married (85.8%) belonging to low socioeconomic strata (70.2%) of the society. Majority (83.8%) of women have a special preference to face book among the various social media sites. There was a statistically significant association between demographic variables such as Age (p value 0.001**), Educational qualification (p value 0.038*), Occupation (p value 0.030*), Socioeconomic status (p value 0.006**) and type of family (p value 0.005**). Conclusion: Although digital revolution has been a boon, this study has revealed a vivid picture regarding cyberbullying, the hidden arena of concerns faced by women